Method for manufacturing negative electrode active material for secondary battery, negative electrode for secondary battery, and lithium secondary battery containing the same
By regulating the granularity distribution of natural graphite and adding carbon coating, improve the mechanical strength and structural stability of the secondary battery negative active material, solve the problem of mechanical stress during the electrode pressure period, significantly improves the life of lithium secondary batteries And output features.
Patent Information
- Application Number
- CN202080006026.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-01-18
- Filing Date
- 2020-01-16
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2040-01-16
AI Technical Summary
In existing secondary batteries, natural graphite is susceptible to mechanical stress during electrode calendering due to its low mechanical strength, which leads to side reactions and swelling with the electrolyte, which in turn affects the life characteristics of the battery.
By adjusting the granularity distribution of the scale -like natural graphite raw materials, and add carbon coating to the electrode active material, control the spherical scale from 0.58 to 1, the vibration density is 1.08g/cc to 1.32g/cc, the maximum particle size distribution of the particle size distribution The difference between the minimum particle size is within the range of 16 μm to 19 μm to improve the structural stability and mechanical strength of the negative active material.
Realize the mechanical stress during the electrode pressure period, reduce the response area of the electrolyte, and prevent the production of gases from swelling and dissolving, thereby significantly improving the life performance and output characteristics of lithium secondary batteries.
Smart Images

Figure GDA0003049321460000171
Abstract
Description
Technical Field
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application is based upon and claims the benefit of priority from Korean Patent Application No. 10-2019-0006690 filed on January 18, 2019 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein in its entirety by reference. Technical Field
[0004] The present invention relates to a method for manufacturing a negative electrode active material for a secondary battery, a negative electrode for a secondary battery, and a lithium secondary battery comprising the same. Background Art
[0005] As energy prices rise due to the depletion of fossil fuels and concerns about environmental pollution increase significantly, environmentally friendly alternative energy sources become an important factor in future life.
[0006] In particular, as technology development and demand for mobile devices increase, demand for secondary batteries as environmentally friendly alternative energy sources is rapidly increasing.
[0007] In secondary batteries, lithium metal was initially used as the negative electrode, but as battery short circuits due to dendrite formation and the resulting risk of explosion became a problem, the use of carbon-based active materials that enable lithium ion intercalation and deintercalation while maintaining structural and electrical properties began to be used.
[0008] As carbon-based active materials, various forms of carbon-based materials such as artificial graphite, natural graphite and hard carbon have been applied, among which the most widely used is a graphite-based active material that can ensure the life characteristics of lithium secondary batteries due to excellent reversibility. Since the graphite-based active material has a low discharge voltage of -0.2V relative to lithium, a battery using the graphite-based active material can exhibit a high discharge voltage of 3.6V, thereby providing many advantages in terms of the energy density of the lithium battery.
[0009] Among them, in particular, natural graphite exhibits high output and capacity characteristics relative to other carbon-based active materials, but natural graphite is subjected to mechanical stress during electrode rolling due to low mechanical strength, whereby side reactions with the electrolyte become strong and life characteristics may deteriorate.
[0010] Therefore, there is a need to develop a natural graphite that can minimize the mechanical stress during electrode compression to prevent side reactions with the electrolyte and swelling phenomena and improve life characteristics.
[0011] Japanese Patent Registration No. 4403327 discloses graphite powder for a negative electrode for a lithium ion secondary battery, but does not propose an alternative to the above-mentioned problems.
[0012] [Prior art literature]
[0013] [Patent Document]
[0014] Japanese Patent Registration No. 4403327 Summary of the invention
[0015]
Technical issues
[0016] One aspect of the present invention provides a negative electrode for a secondary battery, which can improve the output performance of the negative electrode and prevent a side reaction with an electrolyte and a swelling phenomenon, thereby having excellent life characteristics.
[0017] Another aspect of the present invention provides a lithium secondary battery including the negative electrode for a secondary battery.
[0018] Another aspect of the present invention provides a method for manufacturing a negative electrode active material for a secondary battery, which can produce a negative electrode active material with a relatively uniform particle size distribution, improve the output performance of the negative electrode, and prevent side reactions with the electrolyte and swelling to improve life characteristics.
[0019]
Technical solution
[0020] According to an exemplary embodiment of the present invention, a negative electrode for a secondary battery includes: a negative electrode collector; and a negative electrode active material layer, the negative electrode active material layer is formed on the negative electrode collector and includes a negative electrode active material for a secondary battery, wherein the negative electrode active material for a secondary battery includes natural graphite and has a sphericity of 0.58 to 1, a tap density of 1.08 g / cc to 1.32 g / cc, and D 最大 -D 最小 16μm to 19μm, where D 最大 -D 最小 is the maximum particle size D in the particle size distribution 最大 With the minimum particle size D 最小 difference.
[0021] According to another exemplary embodiment of the present invention, a lithium secondary battery includes: the above-mentioned negative electrode for a secondary battery; a positive electrode facing the negative electrode for a secondary battery; a separator interposed between the negative electrode for a secondary battery and the positive electrode; and an electrolyte.
[0022] According to another exemplary embodiment of the present invention, a method for manufacturing a negative electrode active material for a secondary battery includes: adjusting the particle size distribution of a flaky natural graphite raw material; granulating the flaky natural graphite raw material with the adjusted particle size distribution; and adjusting the particle size distribution of the granulated natural graphite, wherein the negative electrode active material comprises natural graphite and has a sphericity of 0.58 to 1, a tap density of 1.08 g / cc to 1.32 g / cc, and D 最大-D 最小 16μm to 19μm, where D 最大 -D 最小 is the maximum particle size D in the particle size distribution 最大 With the minimum particle size D 最小 difference.
[0023]
Beneficial Effects
[0024] The negative electrode for a secondary battery of the present invention comprises a negative electrode active material for a secondary battery, wherein the negative electrode active material for a secondary battery comprises natural graphite and has a sphericity, a tap density and a D 最大 -D 最小 Therefore, the negative electrode can have a higher density, thereby improving the output performance, and at the same time, the mechanical stress experienced by the negative electrode active material during electrode rolling can be minimized, and the reaction area with the electrolyte can be minimized, thereby preventing gas generation and swelling phenomena from occurring, thereby, excellent life performance can be expected. DETAILED DESCRIPTION
[0025] The terms and words used in the present specification and claims should not be interpreted as common meanings or dictionary meanings, but should be interpreted as meanings and concepts that are consistent with the technical ideas of the present invention based on the principle that inventors can appropriately define the concepts of the terms in order to describe their own inventions in the best manner.
[0026] The terms used in this specification are only used to describe exemplary embodiments and are not intended to limit the present invention. Unless the context indicates otherwise, a singular form is intended to include a plural form.
[0027] It should be understood that the terms "comprising", "providing" or "having" used in this specification indicate the existence of implemented features, quantities, steps, constituent elements or a combination thereof, but do not exclude the existence or possibility of adding one or more other features, quantities, steps, constituent elements or a combination thereof.
[0028] In this specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. The average particle size (D 50 ) can be measured using, for example, laser diffraction. By laser diffraction, particle sizes ranging from approximately the submicron range to several millimeters can be measured, and results with high reproducibility and high resolution can be obtained.
[0029] Hereinafter, the present invention will be described in detail.
[0030] <Negative electrode for secondary battery>
[0031] The present invention relates to a negative electrode for a secondary battery, and particularly to a negative electrode for a lithium secondary battery.
[0032] Specifically, the present invention relates to a negative electrode for a secondary battery, comprising: a negative electrode current collector; and a negative electrode active material layer, the negative electrode active material layer is formed on the negative electrode current collector and comprises a negative electrode active material for a secondary battery, wherein the negative electrode active material for a secondary battery comprises natural graphite, and has a sphericity of 0.58 to 1, a tap density of 1.08 g / cc to 1.32 g / cc, and D 最大 -D 最小 16μm to 19μm, where D 最大 -D 最小 is the maximum particle size D in the particle size distribution 最大 With the minimum particle size D 最小 difference.
[0033] The negative electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the lithium secondary battery. For example, as the negative electrode current collector, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used.
[0034] The negative electrode current collector may have fine concavoconvexities formed on its surface to strengthen the binding force to the negative electrode active material, and may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven fabric body.
[0035] The negative electrode current collector may generally have a thickness of 3 μm to 500 μm.
[0036] The negative electrode active material layer is formed on the negative electrode current collector.
[0037] The negative electrode active material layer includes a negative electrode active material for a secondary battery.
[0038] The negative electrode active material for secondary battery includes natural graphite. Since natural graphite exhibits higher output and capacity characteristics than other carbon-based active materials, when using a negative electrode active material including natural graphite, excellent output characteristics and excellent capacity characteristics can be achieved. However, natural graphite has many internal pores, which are blocked during electrode rolling, are subjected to many mechanical stresses, and a passivation film (SEI film) is severely formed during charge / discharge, thereby having poor cyclic swelling performance compared with artificial graphite, etc.
[0039] Therefore, the inventors have repeatedly studied to solve the above-mentioned problems of negative electrode active materials containing natural graphite, and found that the sphericity, tap density and particle size distribution of the negative electrode active material containing natural graphite are controlled within a specific range, thereby improving the rolling characteristics, so that the desired porosity can be achieved even when rolling at a relatively low nip pressure, thereby minimizing particle breakage during rolling, and can effectively reduce the reaction area with the electrolyte to significantly improve the cyclic swelling characteristics.
[0040] Specifically, the negative electrode active material for a secondary battery of the present invention has a sphericity of 0.58 to 1, a tap density of 1.08 g / cc to 1.32 g / cc, and D 最大 -D 最小 16μm to 19μm, where D 最大 -D 最小 is the maximum particle size D in the particle size distribution 最大 With the minimum particle size D 最小 difference.
[0041] Specifically, the sphericity of the negative electrode active material for a secondary battery may be 0.58 to 1, preferably 0.76 to 1. When the sphericity is less than 0.58, it is difficult for the negative electrode to have a higher density, and the electrode adhesion strength decreases so that the life characteristics may be deteriorated, so this is not preferred.
[0042] The sphericity may be defined as a value obtained by dividing the circumference of a circle having the same area as the projected image of the negative electrode active material for a secondary battery by the circumference of the projected image of the negative electrode active material for a secondary battery. Specifically, the sphericity may be defined by the following Formula 1:
[0043] [Formula 1]
[0044] Sphericity = (circumference of a circle having the same area as the projected image of the negative electrode active material for a secondary battery) / (circumference of the projected image of the negative electrode active material for a secondary battery)
[0045] The sphericity can be measured using a particle shape analyzer such as Sysmex FPIA3000 (manufactured by Mavern Inc.) The sphericity according to the present invention may be defined as an average value of sphericities of 10 particles randomly selected from the negative electrode active material.
[0046] On the other hand, the tap density of the negative electrode active material for secondary batteries is 1.08 g / cc to 1.32 g / cc, preferably 1.16 g / cc to 1.24 g / cc. When the tap density is less than 1.08 g / cc, it is difficult for the negative electrode to have a higher density, and the electrode adhesion strength is reduced, so that the life characteristics may be deteriorated, and when the tap density is greater than 1.32 g / cc, the output characteristics may be reduced, so it is not preferred.
[0047] The tap density may be measured by filling a container with the negative electrode active material for a secondary battery, measuring a final volume obtained by vibrating the container a certain number of times, and calculating an apparent density based on the final volume.
[0048] In addition, the negative electrode active material for a secondary battery of the present invention has a maximum particle size D in the particle size distribution. 最大 With the minimum particle size D 最小 Difference D 最大 -D 最小 It may be 16 μm to 19 μm, preferably 17 μm to 18.5 μm.
[0049] When the negative electrode active material D 最大 -D 最小 When D is less than 16 μm, fine powder having a positive influence on output characteristics and electrode adhesion strength may be excessively removed, thereby deteriorating output characteristics and life characteristics. 最大 -D 最小 When it is larger than 19 μm, the uniformity of the particle size is not good, and when the negative electrode active material is used in a negative electrode, the reaction area with the electrolyte may not be sufficiently reduced, so that the effect of improving the swelling characteristics is not significant.
[0050] When the particle size distribution of the negative electrode active material for the secondary battery of the present invention is D 最大 -D 最小 When adjusted to the above range, the particle size can be uniformed to an appropriate level, for example, a particle size distribution diagram can be formed more sharply. Therefore, when the negative electrode active material is used, a negative electrode with a higher density can be formed, so that an improvement in output characteristics can be expected, and a negative electrode can be formed with a relatively small thickness to minimize the rolling process of the electrode and minimize the reaction area with the electrolyte, thereby preventing gas generation and swelling phenomena when operating the negative electrode at an excellent level.
[0051] In addition, the negative electrode active material for a secondary battery may further include a carbon coating layer formed on natural graphite.
[0052] Since the carbon coating can improve the mechanical strength of natural graphite and thus improve the structural stability of the active material, the resistance to mechanical stress to which natural graphite is subjected during rolling can be improved, and the effect of preventing side reactions with the electrolyte can be further improved.
[0053] Based on the total weight of the negative electrode active material for the secondary battery, the content of the carbon coating can be 3.5 wt % to 8 wt %, preferably 4 wt % to 6 wt %. Within this range, the mechanical strength can be further improved and the migration resistance of lithium will not increase excessively, so it is preferred in achieving output characteristics.
[0054] The carbon coating layer may be formed by providing one or more materials selected from the group consisting of coal tar pitch, rayon and polyacrylonitrile resin or precursors of the materials on the surface of natural graphite particles, and then thermally decomposing the materials. Preferably, the carbon coating layer contains soft carbon, which can be formed by the firing and thermal decomposition process of coal tar pitch. The heat treatment process for forming the carbon coating layer may be performed at a temperature range of 1,000° C. to 4,000° C. in terms of forming a uniform carbon coating layer and preventing excessive formation of the carbon coating layer.
[0055] The average particle size (D 50 ) can be 8μm to 16μm, preferably 10μm to 14μm. When a negative electrode active material having an average particle size within this range is used in the positive electrode, the reaction area with the electrolyte can be reduced, thereby maximizing the effect of preventing side reactions with the electrolyte.
[0056] D 最大 , D 最小 , average particle size (D 50 ) and the like can be measured by analyzing the particle size distribution of the negative electrode active material. The particle size distribution can be analyzed using a particle size distribution measuring device such as Mastersizer 2000 (manufactured by Malvern Corporation).
[0057] The negative electrode active material of the present invention as described above can be produced by, for example, a production method including the steps of: adjusting the particle size distribution of a flaky natural graphite raw material; granulating the flaky natural graphite raw material having the adjusted particle size distribution; and adjusting the particle size distribution of the granulated natural graphite.
[0058] First, a flaky natural graphite raw material as a raw material of the negative electrode active material of the present invention is prepared, and fine powder and coarse powder are removed to adjust the particle size distribution of the flaky natural graphite raw material. Here, the particle size distribution of the flaky natural graphite raw material can be adjusted by a method for adjusting the particle size distribution of particles known in the art, such as filtering. For example, the particle size of the flaky natural graphite raw material can be adjusted so that, approximately, the average particle size is 100nm to 400nm, preferably 200nm to 300nm, and D 最大 -D 最小 The thickness is 150 nm to 400 nm, preferably 150 nm to 300 nm, but the present invention is not limited thereto.
[0059] When the step of adjusting the particle size distribution of the flaky graphite raw material as the raw material is performed, natural graphite having a relatively uniform particle size distribution can be produced in the granulation step described later.
[0060] Next, the flaky natural graphite raw material with adjusted particle size distribution is mixed with binder pitch and agglomerated.
[0061] The binder pitch is added to promote the aggregation of the flaky natural graphite raw material, and may be at least one selected from the group consisting of petroleum-based pitch and coal-based pitch.
[0062] The flaky natural graphite raw material and the binder pitch may be mixed in a weight ratio of 85:15 to 99:1, preferably 90:10 to 97:3.
[0063] The granulation of the flaky natural graphite raw material and the binder pitch may be performed at 2,000° C. to 3,000° C., preferably 2,200° C. to 2,800° C., to smoothly granulate therebetween.
[0064] The granulation of the flaky natural graphite raw material and the binder pitch may be performed while rotating the mixture of the flaky natural graphite raw material and the binder pitch at a speed of 1,000 to 4,000 rpm, preferably 2,000 to 3,000 rpm, so as to be smoothly granulated and sufficiently agglomerated.
[0065] The granulation of the flaky natural graphite raw material and the binder pitch may be performed for 3 to 15 hours, preferably 5 to 10 hours, so that they are smoothly granulated and fully agglomerated.
[0066] The natural graphite granulated as described above may have an average particle size (D) of approximately 8 to 16 μm, preferably 10 to 14 μm. 50 ), and D of 10 μm to 35 μm, preferably 14 μm to 26 μm 最大 -D 最小 , but the present invention is not limited to this.
[0067] Next, a step of adjusting the particle size distribution of the granulated natural graphite is performed.
[0068] Here, the step of adjusting the particle size distribution of the granulated natural graphite may be performed by a method for adjusting the particle size distribution of particles known in the art, such as sieving.
[0069] According to need, after the step of adjusting the particle size distribution of the granulated natural graphite, a step of forming a carbon coating layer on the natural graphite may be further performed, whereby the mechanical strength and structural stability of the natural graphite may be improved.
[0070] The carbon coating layer may be formed by providing one or more materials selected from the group consisting of coal tar pitch, rayon and polyacrylonitrile resin or precursors of the materials on the surface of natural graphite particles, and then thermally decomposing the materials. Preferably, the carbon coating layer contains soft carbon, which may be formed by the firing and thermal decomposition process of coal tar pitch. The heat treatment process for forming the carbon coating layer may be performed at a temperature range of 1,000° C. to 4,000° C. in terms of forming a uniform carbon coating layer and preventing excessive formation of the carbon coating layer.
[0071] On the other hand, the negative electrode active material layer may further include one or more additives selected from the group consisting of a binder, a thickener, and a conductive material in addition to the negative electrode active material for a lithium secondary battery.
[0072] The binder may be generally contained in an amount of 1 wt % to 30 wt % based on the total weight of the negative electrode active material layer as a component that facilitates bonding of a conductive material, an active material, a negative electrode current collector, and the like.
[0073] The binder may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber or a combination of two or more thereof.
[0074] As the thickener, all thickeners conventionally used in lithium secondary batteries can be used, and for example, carboxymethyl cellulose (CMC) and the like can be used.
[0075] The thickener may be included in an amount of 1 wt % to 30 wt % based on the total weight of the negative active material layer.
[0076] The conductive material is a component for further improving conductivity of the negative electrode active material, and the content of the conductive material may be 1 wt % to 30 wt % based on the total weight of the negative electrode active material layer.
[0077] The conductive material is not particularly limited as long as it has conductivity without causing chemical changes in the battery, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black and thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as fluorocarbon powders, aluminum powders and nickel powders, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, conductive materials such as polyphenylene derivatives, etc. Specific examples of commercially available conductive materials include acetylene black series such as products of Chevron Chemical Company, Denka Black of Denka Singapore Private Limited, products of Gulf Oil Company, Ketjen Black EC series of Armak, Vulcan XC-72 of Cabot Company, Super P of Timcal, etc.
[0078] The negative electrode active material layer may be prepared by mixing the above negative electrode active material for lithium secondary battery with at least one additive selected from a binder, a conductive material and a thickener in a solvent to prepare a negative electrode slurry, applying the negative electrode slurry on a negative electrode collector, and rolling and drying the applied slurry.
[0079] The solvent may include water or an organic solvent such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount in which a slurry comprising a negative electrode active material and optional binders, conductive materials, etc., and the solvent has a preferred viscosity. For example, the solvent may be included in an amount in which the solid content comprising the negative electrode active material for a secondary battery and optional binders, thickeners, and conductive materials is 50% to 95% by weight, preferably 70% to 90% by weight.
[0080] <Lithium Secondary Battery>
[0081] Furthermore, the present invention provides a lithium secondary battery including the above-mentioned negative electrode for a secondary battery.
[0082] Specifically, the lithium secondary battery includes: the above-mentioned negative electrode for the secondary battery; a positive electrode facing the negative electrode for the secondary battery; a separator interposed between the negative electrode for the secondary battery and the positive electrode; and an electrolyte.
[0083] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector.
[0084] The positive electrode active material layer includes a positive electrode active material and optionally a binder and a conductive material.
[0085] The positive electrode current collector is not particularly limited as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used.
[0086] The positive electrode current collector may generally have a thickness of 3 μm to 500 μm.
[0087] The positive electrode active material layer is formed on the positive electrode current collector and includes a positive electrode active material.
[0088] The positive electrode active material is a compound capable of reversibly inserting and deinserting lithium, and may specifically include a lithium composite metal oxide containing one or more metals such as cobalt, manganese, nickel or aluminum and lithium. More specifically, examples of the lithium composite metal oxide may include lithium manganese oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium cobalt oxides (e.g., LiCoO2, etc.), lithium nickel oxides (e.g., LiNiO2, etc.), lithium nickel manganese oxides (e.g., LiNi 1-Y Mn Y O2 (where 0<Y<1), LiMn 2-z Ni z O4 (where 0<Z<2), etc.), lithium nickel cobalt oxides (such as LiNi 1-Y1 Co Y1 O2 (where 0<Y1<1), etc.), lithium manganese cobalt oxides (such as LiCo 1-Y2 Mn Y2 O2 (where 0<Y2<1), LiMn 2-z1 Co z1 O4 (where 0<Z1<2), etc.), lithium nickel manganese cobalt oxides (such as Li(Ni p Co q Mn r1 )O2 (where 0<p<1, 0<q<1, 0<r1<1, and p+q+r1=1) or Li(Ni p1 Co q1 Mn r2 )O4 (where 0<p1<2, 0<q1<2, 0<r2<2, and p1+q1+r2=2), etc.), or lithium nickel cobalt transition metal (M) oxide (such as Li(Ni p2 Co q2 Mn r3 M S2)O2 (wherein M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg and Mo; and p2, q2, r3 and s2 are the atomic fractions of each independent element, and 0<p2<1, 0<q2<1, 0<r3<1, 0<s2<1, p2+q2+r3+s2=1), etc.), etc., and may contain any one or more compounds thereof. Among them, from the viewpoint of increasing the capacity characteristics and safety characteristics of the battery, the lithium composite metal oxide may be LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (for example, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2、Li(Ni 0.5 Mn 0.3 Co 0.2 )O2 or Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.) or lithium nickel cobalt aluminum oxide (e.g. Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.
[0089] The positive electrode active material may be contained in an amount of 80 wt % to 99 wt % based on the total weight of the positive electrode active material layer.
[0090] The positive electrode active material layer may optionally contain at least one additive selected from the group consisting of a binder and a conductive material in addition to the positive electrode active material described above.
[0091] The binder is a component that helps to bind the active material, the conductive material, etc. and to the current collector, and is generally added in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer. Examples of the binder include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, various copolymers, etc.
[0092] The conductive material is not particularly limited as long as it has conductivity without causing chemical changes in the battery, for example, graphite can be used; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers such as carbon fibers or metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. Specific examples of commercially available conductive materials include acetylene black series such as products of Chevron Chemical Company, Danka Black of Danka Singapore Pte Ltd, products of Gulf Oil Company, Ketjen Black EC series of Armak Company, Vulcan XC-72 of Cabot Company, Super P of Temeco Company, etc.
[0093] The conductive material may be included in an amount of 1 wt % to 30 wt % based on the total weight of the positive electrode active material layer.
[0094] The positive electrode active material layer may be manufactured by adding a positive electrode active material and optionally an additive including a binder and / or a conductive material to a solvent to prepare a positive electrode slurry, applying the slurry on a positive electrode collector, and rolling and drying the applied slurry.
[0095] The solvent may include an organic solvent such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount in which a solution comprising a positive electrode active material and an optional binder, a conductive material, etc., and the solvent has a preferred viscosity. For example, the solvent may be included in an amount in which the solid content comprising the positive electrode active material and the optional binder and conductive material is 50% to 95% by weight, preferably 70% to 90% by weight.
[0096] In the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a transmission channel for lithium ions, and any separator can be used without particular limitation, as long as it is commonly used as a separator in a lithium secondary battery. In particular, it is preferred that the ion transport of the electrolyte has low resistance and has excellent electrolyte impregnation ability. Specifically, a porous polymer film can be used, for example, a porous polymer film made of polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure of two or more films thereof. In addition, conventional porous non-woven fabrics can be used, such as glass fibers with high melting points, non-woven fabrics made of polyethylene terephthalate fibers, etc. In addition, a coated separator containing a ceramic component or a polymer material in order to ensure heat resistance or mechanical strength can be used, optionally as a single layer or multilayer structure.
[0097] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc. that can be used to manufacture lithium secondary batteries, but are not limited thereto.
[0098] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0099] As the organic solvent, any organic solvent can be used without particular limitation, as long as it can be used as a medium in which ions involved in the electrochemical reaction of the battery can move. Specifically, as the organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (wherein R is a linear, branched or cyclic C2-C20 hydrocarbon group, and may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or sulfolanes, etc. can be used. Wherein, preferably use carbonate solvent, more preferably have high ion conductivity and high dielectric constant to increase the charge / discharge performance of battery cyclic carbonate (for example, ethylene carbonate, propylene carbonate etc.) and have low viscosity linear carbonate compound (for example, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate etc.) mixture.In this case, when cyclic carbonate and chain carbonate are mixed and used with the volume ratio of about 1:1 to about 1:9, the performance of electrolyte can be excellent.
[0100] The lithium salt can be used without particular limitation, as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, as the lithium salt, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. can be used. Preferably, the concentration of the lithium salt is in the range of 0.1M to 2.0M. When the concentration of the lithium salt is within this range, the electrolyte has appropriate conductivity and viscosity, so that the electrolyte can exhibit excellent electrolyte properties, and the lithium ions can be effectively moved.
[0101] As described above, the secondary battery according to the present invention can be used in portable devices such as mobile phones, notebook computers and digital cameras, electric vehicle fields such as hybrid electric vehicles (HEV), etc., and in particular, can be preferably used as a configuration cell of a medium-to-large battery module. Therefore, the present invention also provides a medium-to-large battery module comprising the secondary battery as described above as a unit cell.
[0102] The medium and large-sized battery module may be preferably applied to power sources requiring large output and large capacity, such as electric vehicles, hybrid electric vehicles, and power storage devices.
[0103] Hereinafter, embodiments of the present invention will be described in detail so as to be easily implemented by those skilled in the art to which the present invention belongs. However, the present invention can be implemented in various forms and is not limited to the embodiments provided in this specification.
[0104] Example
[0105] Example 1: Production of negative electrode for secondary battery
[0106] <Manufacturing of positive electrode active material for secondary battery>
[0107] A flaky natural graphite raw material was prepared, and fine powder and coarse powder were removed by filtration to adjust the particles to have an average particle size (D 50 ) and 200nm D 最大 -D 最小 The flaky natural graphite raw material and binder pitch (petroleum pitch) were mixed at a weight ratio of 95:5, rotated at 2,500 rpm for 8 hours at 2,500°C, and agglomerated and granulated to produce granulated natural graphite (average particle size (D 50 ) is 11 μm, D 最大 -D 最小 =22μm).
[0108] The granulated natural graphite was subjected to particle screening to remove fine powder and coarse powder, thereby adjusting the particle size distribution. Coal tar pitch was mixed with the natural graphite whose particle size distribution was adjusted, and fired at 2,500° C. to produce a secondary battery negative electrode active material having a carbon coating of soft carbon formed on the natural graphite. The carbon coating of soft carbon was formed at 4.5 wt % based on the total weight of the negative electrode active material for the secondary battery.
[0109] The negative electrode active material for secondary battery was measured, and the sphericity was 0.8, the tap density was 1.2 g / cc, and the average particle size (D 50 ) is 11 μm, and D 最大 -D最小 It is 17.5μm.
[0110] <Manufacturing of negative electrode for secondary battery>
[0111] The negative electrode active material for secondary battery manufactured above, Super C65 as a conductive material, styrene-butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener were mixed at a weight ratio of 96.6:1:1.3:1.1, and water was added thereto to prepare a negative electrode slurry.
[0112] The negative electrode slurry prepared as above was applied to a copper current collector and vacuum dried at about 130° C. for 10 hours to produce a negative electrode for a secondary battery of Example 1. Here, the loading capacity of the negative electrode was 3.61 mAh / cm 2 .
[0113] Examples 2 to 7 and Comparative Examples 1 to 5
[0114] In addition to adjusting the process conditions during the removal of fine powder and coarse powder so that the negative electrode active material has the sphericity, tap density, average particle size (D 50 ) and D 最大 -D 最小 Otherwise, negative electrode active materials of Examples 2 to 7 and Comparative Examples 1 to 5 were manufactured in the same manner as in Example 1. Next, negative electrodes of Examples 2 to 7 and Comparative Examples 1 to 5 were manufactured in the same manner as in Example 1 using the manufactured negative electrode active materials.
[0115] [Table 1]
[0116]
[0117] The sphericity, tap density, average particle size (D 50 ) and D 最大 -D 最小 .
[0118] (1) Sphericity
[0119] The sphericity of the negative electrode active materials for secondary batteries used in Examples and Comparative Examples was measured using a particle shape analyzer (sysmex FPIA3000, manufactured by Mavern Co. The sphericity was expressed as the average sphericity of 10 particles randomly selected from the negative electrode active materials for secondary batteries.
[0120] The sphericity is defined as a value obtained by dividing the circumference of a circle having the same area as the projected image of the negative electrode active material for a secondary battery by the circumference of the projected image of the negative electrode active material for a secondary battery, and is specifically defined by the following Formula 1:
[0121] [Formula 1]
[0122] Sphericity = (circumference of a circle having the same area as the projected image of the negative electrode active material for a secondary battery) / (circumference of the projected image of the negative electrode active material for a secondary battery)
[0123] (2) Tap density
[0124] The tap density can be measured by filling a container with the secondary battery negative active material, measuring a final volume obtained by vibrating the container 2,000 times, and calculating the apparent density based on the final volume.
[0125] (3) Average particle size (D 50 ), D 最大 -D 最小
[0126] The average particle size (D 50 ) and D 最大 -D 最小 .
[0127] Experimental example
[0128] <Manufacturing of lithium secondary batteries>
[0129] LiCoO2 as a positive electrode active material, Li-435 (manufactured by Danka) as a conductive material, KF9700 (manufactured by Kureha) as a binder, and BH-730H (manufactured by Zeon) were mixed in a weight ratio of 96.25:1.0:1.5:1.25, water was added thereto to prepare a positive electrode slurry, and the positive electrode slurry was applied to an aluminum foil, which was vacuum dried and rolled at about 130°C for 8 hours to manufacture a positive electrode. Here, the positive electrode was manufactured so that its loading capacity was 3.61 mAh / cm 2 .
[0130] A polyolefin separator was interposed between each negative electrode and positive electrode manufactured in Examples 1 to 7 and Comparative Examples 1 to 5, and an electrolyte solution in which 1M LiPF6 was dissolved in a non-aqueous electrolyte solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) mixed in a volume ratio of 1:4 was injected to manufacture the lithium secondary batteries of the Examples and Comparative Examples.
[0131] Experimental Example 1: Evaluation of Swelling
[0132] The lithium secondary batteries of Examples 1 to 7 and Comparative Examples 1 to 5 manufactured as above were charged and discharged in the charging range of SOC 0 to SOC 95, with 0.1 C for the 1st cycle, 0.2 C for the 2nd cycle, and 0.5 C for the 3rd to 30th cycles. Thereafter, the swelling ratio was measured by the following Formula 1:
[0133] [Formula 1]
[0134] Swelling ratio (%) = {(d2-d1) / d1} × 100
[0135] Here, d1 is the thickness of the negative electrode for a secondary battery before performing the 1st charge / discharge cycle, and d2 is the thickness of the negative electrode for a secondary battery after performing the 30th charge / discharge cycle.
[0136] [Table 2]
[0137] Swelling ratio (%) Example 1 21.0 Example 2 21.3 Example 3 21.6 Example 4 22.1 Example 5 22.5 Example 6 23.8 Example 7 24.7 Comparative Example 1 32.3 Comparative Example 2 34.7 Comparative Example 3 33.2 Comparative Example 4 37.6 Comparative Example 5 38.5
[0138] Referring to Table 2, the tap density, sphericity and D 最大 -D 最小 The secondary battery negative electrode and lithium secondary battery of the secondary battery negative electrode active material of the embodiments of the range have excellent tolerance to mechanical stress and minimized reaction area with the electrolyte, thereby confirming that gas generation and swelling phenomena are prevented to an excellent level during negative electrode operation compared with the comparative example.
[0139] Experimental Example 2: Output Evaluation
[0140] The output characteristics of the secondary batteries of Examples 1 to 7 and Comparative Examples 1 to 5 manufactured as above were evaluated. The output characteristics were evaluated by setting the secondary batteries of Examples and Comparative Examples to SOC 50 according to a hybrid pulse power characteristic (HPPC) test and measuring the output resistance at room temperature (25°C).
[0141] Specifically, the secondary battery was charged and discharged for 3 cycles at 0.33 C under the conditions of 2.5 V discharge and 4.2 V charge. Thereafter, the battery was charged (10 minutes) at 2.5 C, stopped (30 minutes), discharged (10 minutes) at 2.5 C, and stopped (30 minutes) from the state of being discharged to SOC 50, and the voltage change during charge / discharge was divided by the applied current to measure the output resistance.
[0142] [Table 3]
[0143] Output resistance (ohms) Example 1 0.85 Example 2 0.87 Example 3 0.90 Example 4 0.94 Example 5 0.97 Example 6 1.01 Example 7 1.03 Comparative Example 1 1.45 Comparative Example 2 1.42 Comparative Example 3 1.38 Comparative Example 4 1.67 Comparative Example 5 1.75
[0144] Referring to Table 3, it was confirmed that the tap density, sphericity and D 最大 -D 最小 The negative electrode for a secondary battery and the lithium secondary battery of the negative electrode active material for a secondary battery of the examples of the range had higher energy density and output characteristics than those of the comparative examples.
Claims
1. A negative electrode for a secondary battery, comprising: a negative electrode current collector; and a negative electrode active material layer formed on the negative electrode current collector and containing a negative electrode active material for a secondary battery, The negative electrode active material for a secondary battery comprises natural graphite and has a sphericity of 0.58 to 1, a tap density of 1.08 g / cc to 1.32 g / cc, and D 最大 -D 最小 16μm to 19μm, where D 最大 -D 最小 is the maximum particle size D in the particle size distribution 最大 With the minimum particle size D 最小 The difference between the negative electrode active material and the negative electrode active material for the secondary battery has an average particle size D of 8 μm to 16 μm. 50 , The sphericity is measured using a particle shape analyzer and represents the average value of the sphericity of 10 particles randomly selected from the negative electrode active material, and the sphericity is defined by the following formula: Sphericity = (circumference of a circle having the same area as the projected image of the negative electrode active material for a secondary battery) / (circumference of the projected image of the negative electrode active material for a secondary battery), The average particle size D 50 is defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve, and Where D 最大 , D 最小 , D 50 The particle size distribution of the negative electrode active material was respectively measured by analyzing the particle size distribution of the negative electrode active material using a particle size distribution measuring device. 2 . The negative electrode for a secondary battery according to claim 1 , wherein the negative electrode active material for a secondary battery has a sphericity of 0.76 to 1. 3 . 3 . The negative electrode for a secondary battery according to claim 1 , wherein the negative electrode active material for a secondary battery has a tap density of 1.16 g / cc to 1.24 g / cc.
4. The negative electrode for a secondary battery according to claim 1, wherein In the particle size distribution of the negative electrode active material for secondary battery, D 最大 -D 最小 17μm to 18.5μm, where D 最大 -D 最小 The maximum particle size D 最大 With the minimum particle size D 最小 difference. 5 . The negative electrode for a secondary battery according to claim 1 , wherein the negative electrode active material for a secondary battery further comprises a carbon coating layer formed on the natural graphite. 6 . The negative electrode for a secondary battery according to claim 5 , wherein the carbon coating layer comprises soft carbon. 7 . The negative electrode for a secondary battery according to claim 5 , wherein the negative electrode active material for a secondary battery comprises 3.5 wt % to 8 wt % of the carbon coating layer.
8. A lithium secondary battery, comprising: The negative electrode for a secondary battery according to claim 1; a positive electrode facing the negative electrode for a secondary battery; a separator interposed between the negative electrode for the secondary battery and the positive electrode; and Electrolytes.
9. A method for manufacturing a negative electrode active material for a secondary battery, the method comprising: Adjust the particle size distribution of flaky natural graphite raw materials; granulating the flaky natural graphite raw material with adjusted particle size distribution; as well as Adjusting the particle size distribution of the granulated natural graphite, The negative electrode active material comprises natural graphite and has a sphericity of 0.58 to 1, a tap density of 1.08 g / cc to 1.32 g / cc, and D 最大 -D 最小 16μm to 19μm, where D 最大 -D 最小 is the maximum particle size D in the particle size distribution 最大 With the minimum particle size D 最小 The difference between the negative electrode active material and the negative electrode active material for the secondary battery has an average particle size D of 8 μm to 16 μm. 50 , The sphericity is measured using a particle shape analyzer and represents the average value of the sphericity of 10 particles randomly selected from the negative electrode active material, and the sphericity is defined by the following formula: Sphericity = (circumference of a circle having the same area as the projected image of the negative electrode active material for a secondary battery) / (circumference of the projected image of the negative electrode active material for a secondary battery), The average particle size D 50 is defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve, and Where D 最大 , D 最小 , D 50 The particle size distribution of the negative electrode active material was respectively measured by analyzing the particle size distribution of the negative electrode active material using a particle size distribution measuring device.
10. The method for manufacturing a negative electrode active material for a secondary battery according to claim 9, further comprising: After adjusting the particle size distribution of the granulated natural graphite, a carbon coating is formed on the natural graphite.
Citation Information
Patent Citations
Optical component, camera module and optical apparatus
KR1020190006690A
Nonaqueous secondary battery carbon material, nonaqueous secondary battery anode, and lithium ion secondary battery
JP2013197082A
Carbon material, and nonaqueous secondary battery
JP2016111021A
Carbon material for nonaqueous secondary battery and lithium ion secondary battery
JP2016136517A
Method for producing negative electrode material for nonaqueous secondary battery and nonaqueous secondary battery using negative electrode material for nonaqueous secondary battery
JP2017126426A